2020
DOI: 10.1111/jcmm.15244
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of deep sequencing exosome‐microRNA expression profile derived from CP‐II reveals potential role of gga‐miRNA‐451 in inflammation

Abstract: Mycoplasma gallisepticum (MG) can cause chronic respiratory disease (CRD) in chickens. While several studies have reported the inflammatory functions of microRNAs during MG infection, the mechanism by which exosomal miRNAs regulate MG‐induced inflammation remains to be elucidated. The expression of exosome‐microRNA derived from MG‐infected chicken type II pneumocytes (CP‐II) was screened, and the target genes and function of differentially expressed miRNAs (DEGs) were predicted. To verify the role of exosomal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 49 publications
1
13
0
Order By: Relevance
“…The results showed that some items of biological process were involved in regulating cellular process, single-organism process and metabolic process; some items of cellular component were involved in regulating cell part, intracellular membrane-bounded organelle; and some items of molecular functions were involved in regulating protein binding, organic cyclic compound binding and catalytic activity as reported elsewhere (Zhao et al, 2020).…”
Section: Figure 3 Go Database Function Notessupporting
confidence: 70%
“…The results showed that some items of biological process were involved in regulating cellular process, single-organism process and metabolic process; some items of cellular component were involved in regulating cell part, intracellular membrane-bounded organelle; and some items of molecular functions were involved in regulating protein binding, organic cyclic compound binding and catalytic activity as reported elsewhere (Zhao et al, 2020).…”
Section: Figure 3 Go Database Function Notessupporting
confidence: 70%
“…Emerging evidence demonstrates P-gp-related exosomal miRNAs can lead to long-term P-gp expression in recipient cells [ 52 ]. For example, exosomal miRNA-451 and miRNA-27a are abundant in recipient cells, which could explain these long-term effects [ 53 ].…”
Section: The Functions Of Exosomal Mirnas In Cancermentioning
confidence: 99%
“…All RNA oligonucleotides were designed and synthesized by GenePharm (Shanghai, China) and are shown in Table 2. [53]. Brie y, it was prepared from lung tissue of 15 day SPF chicken embryos.…”
Section: Microrna Target Prediction and Sequencesmentioning
confidence: 99%